Evaluation of agricultural wastes for the cultivation of Pleurotus eryngii (DC. ex Fr.) Quel. var. ferulae Lanzi - Kirbag, Sevda; Akyuz, Mehmet (Academic Journals, 2008)
This study investigated the possible use of local agricultural wastes for the cultivation of Pleurotus eryngii var. ferulae. For the propagation of the main culture, 2.0% malt-extract agar was used whereas wheat grains were used for the propagation of spawn. For the formation of basidiocarp, wheat straw (WS), cotton straw (CS), lentil straw (LS) and rice bran (RB) were used as culture media. Eight types of compost were prepared: a mixture of WS-CS, WS-CS + 10% RB, WS-CS + 20% RB, WS + 10% LS, WS + 20% LS, WS + 10% RB, WS + 20% RB and WS. The shortest mycelium growing period was determined as 9.2 days on WS-CS (1: 1) + 20.0% RB and the longest period was 13.0 days on WS + 20.0% RB. The shortest primordium formation period was 97.4 days on WS-CS (1: 1), while the longest period was 110.4 days on WS + 20.0% RB. The shortest harvest period was 117.2 days on WS-CS (1: 1) + 10.0% RB, and the longest period was 125.8 days on WS + 20% RB. The highest biological efficiency (BE) was 77.2% on WS-CS (1: 1) + 20.0% RB, while the lowest BE was 48.6% on WS-CS (1: 1). The lowest yield per 100 g of material (70% moisture) was 14.6 g on WS-CS (1: 1) and the highest yield was 23.2 g on WS-CS (1: 1) + 20.0% RB. In conclusion, various local agricultural wastes can be used for the cultivation of P. eryngii var. ferulae.
Keywords: Cultivation; Pleurotus eryngii var. ferulae; agricultural wastes; yield